PENGARUH PEMBERIAN JAMU TRADISIONAL TERHADAP BOBOT HIDUP, BOBOT KARKAS, BOBOT GIBLET DAN LEMAK ABDOMINAL BROILER - Tama, Cheldra Aji; Septinova, Dian; Kurtini, Tintin (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
This study aims to determine the effect of traditional on herbal on live weight, carcass weight, giblet and abdominal fat weight of broiler. This study uses a completely randomized design (CRD) with three treatments and six replications. The treatments were water (P0), juice of turmeric water (P1), and boiled guava leaves and betel leaf (P2). One broiler is taken from each experimental unit for carcas. The observed variables were live weight, carcass weight, giblet weight and abdominal fat weight of Broiler. Each treatment was applied to 14-28 days age broiler.The results showed that the traditional herbal medicine no significant effect (P> 0.05) on live weight, carcass weight, giblet weight and abdominal fat weigh of broiler. Keywords: Traditional Herbal Medicine, Live Weight, Carcass Weight, Giblet Weights, and Abdominal Fat weight of Broilers